Biological Methods for Cell-Cycle Synchronization of Mammalian Cells. (June 2001) - Davis, Penny K.; Ho, Alan; Dowdy, Steven F.
Understanding the molecular and biochemical basis of cellular growth and division involves the investigation of regulatory events that most often occur in a cell-cycle phase-dependent fashion. Studies examining cell-cycle regulatory mechanisms and progression invariably require cell-cycle synchronization of cell populations. Thus, many methods have been established to synchronize cells at specific phases of the cell cycle. Several of the common methods involve pharmacological agents, which act at various points throughout the cell cycle. Because of adverse cellular perturbations resulting from many of the synchronizing drugs used, other synchrony methods that involve less perturbation of biological systems, such as serum deprivation, contact inhibition, and centrifugal elutriation have a significant advantage. The advantages and disadvantages of these cell synchronization methods are discussed in this review.